2018
DOI: 10.1111/1365-2745.13073
|View full text |Cite
|
Sign up to set email alerts
|

Twelve years of low nutrient input stimulates growth of trees and dwarf shrubs in the treeline ecotone

Abstract: Almost all natural terrestrial ecosystems are nutrient limited in terms of growth, and we expect treeline vegetation to be no exception. However, direct constraints of low temperature on tissue formation may superimpose effects of low nutrient availability. We examined growth responses of two tree (Larix decidua and Pinus uncinata) and two dwarf shrub species (Vaccinium myrtillus and Vaccinium gaultherioides) to 12 years of moderate fertilizer addition (NPK applied at a rate of 15 and 30 kg nitrogen ha−1 a−1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…We assume that the temperature effect on N cycling and N supply and resulting reductions in leaf area (and possibly photosynthetic capacity) represent a major pathway through which elevation is acting on total C gain. In addition, tree growth was found to be stimulated by moderate nitrogen fertilization at the tree line ecotone in the Swiss Alps (Möhl et al 2018 ), supporting our assumption of nutrient limitation of aboveground tree productivity at high elevations. The replacement of macrophyllous, broadleaved trees by southern hemispheric conifers at the upper montane zone and ericoid trees with more sclerophyllous leaves and their specialized ericoid mycorrhiza at the subalpine zone can also be interpreted as an indication of increasing nutrient limitation at higher elevations.…”
Section: Discussionsupporting
confidence: 86%
“…We assume that the temperature effect on N cycling and N supply and resulting reductions in leaf area (and possibly photosynthetic capacity) represent a major pathway through which elevation is acting on total C gain. In addition, tree growth was found to be stimulated by moderate nitrogen fertilization at the tree line ecotone in the Swiss Alps (Möhl et al 2018 ), supporting our assumption of nutrient limitation of aboveground tree productivity at high elevations. The replacement of macrophyllous, broadleaved trees by southern hemispheric conifers at the upper montane zone and ericoid trees with more sclerophyllous leaves and their specialized ericoid mycorrhiza at the subalpine zone can also be interpreted as an indication of increasing nutrient limitation at higher elevations.…”
Section: Discussionsupporting
confidence: 86%
“…Although temperature has been suggested as a primary driver underlying the formation of such boundaries [20], low soil nutrient availability may also be responsible for reduced growth of trees and shrubs at their upper limits [21]. A recent study found that the growth of trees and shrubs in an alpine ecosystem increased with slightly increased nutrient availability [22], which in turn suggesting the potential increasing nutrient dynamics with the expansion of trees or shrubs. Thus, understanding changes of N cycling at alpine ecosystems is particularly important as both alpine treelines and shrublines may shift in the face of global climate change [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…2013). These highland nutrient limitations are further supported by field experiments in which fertilization stimulated highland forest growth (Möhl 2019). Therefore, highland nutrient limitation could determine upper limits to plant distributions (Rehm and Feeley 2015).…”
Section: Discussionmentioning
confidence: 77%